Study on Heat Transfer and Flow Characteristics of a Multi- unit Parallel- flow Type Condenser - 包涛; 陈蕴光; 董玉军; 袁秀玲; 董晓俊 (Zhileng xuebao)
For parallel - flow type condensers, the louvered fin is adopted for air side and the micro- channel with rectangle sections and small hydraulic diameter is adopted for refrigerant side. The formulas suitable to this special configuration were presented to calculate the heat transfer coefficient and pressure drop. Then the mathematic model was established to simulate the performance of the condenser. The results show that during the process of flow and condensation of the refrigerant, surface tension plays a significant role in the enhancement of heat transfer. In the parallel flow type condenser with gradually decreasing flow section areas, it can keep high heat transfer coefficient and low pressure - drop.